Early literacy matters - Canady, Carol E.; Canady, Robert Lynn (CRC Press, 2021)
"Early Literacy Matters is an innovative action guide for elementary school leaders and instructional coaches dedicated to accelerating literacy performance in the early grades, when prevention of reading difficulties matters most. As a unique father-daughter team with combined expertise in literacy education and instructional leadership, the authors share best practices for literacy success. Readers will learn how to... establish and lead a literacy team, implement embedded professional development, utilize key assessments to frame daily instruction, and illustrate specific organizational and scheduling models needed to support systemic change based on the science of reading. Each chapter features reflection questions and explicit strategies and tools leaders can implement immediately in today's classrooms"--
Keywords: Language arts (Early childhood)